Збирання незернової частини врожаю комбайном обчісувального типу - Шегеда, К. О.; Шокарев, Олександр Миколайович; Болтянський, Борис Володимирович; Шокарев, О. О.; Sheheda, K.; Shokarev, Oleksandr; Boltianskyi, Borys; Shokarev, O. (Мелітополь : ТДАТУ, 2022)
UA: До нових технологій комбайнового збирання зернових культур відноситься і метод обчісування рослин на корені. Однак основним стримуючим чинником щодо широкого впровадження у виробництво нової зернозбиральної техніки залишається проблема збирання обчесаного на корені стеблостою. Для збирання обчесаного на корені стеблостою найбільш придатні такі типи пристроїв, як ріжучий пристрій сегментного типу з транспортуючим механізмом, шнековий ріжучий пристрій та роторний ріжучій пристрій. Розглянуто способи та засоби збирання незернової частини врожаю комбайном очисного типу. Вирішена задача вдосконалення різального пристрою, в якому шляхом модернізації конструктивно-технологічної схеми, основаної на новій сукупності конструктивних елементів, їх взаємному розташуванні і наявності зв’язків між ними, забезпечується збільшення продуктивності різального пристрою, підвищення надійності технологічного процесу зрізання та валко утворення зрізаних стеблин. Наведена загальна методика вибору ріжучого пристрою в залежності від культури, що забирається, і технології збору зрізаних стебел. EN: Currently, the main method of harvesting crops is separate and direct combining. However, the creation of a combine with a classic scheme of threshing machine increased capacity is accompanied by an increase in its metal content, energy consumption and size. Almost three quarters of the power is spent on interrupting, shaking the straw. New, less energy-intensive technologies include combine harvesting of crops by the method of combing at the root. However, the question of harvesting the non-grain part of the crop in this technological process remains open. Combed plants left in the field in the form of uncut mass interfere with the work of tillage implements. When laying uncrushed straw in the soil, it contributes to the accumulation in the arable layer of organic matter that has not decomposed, which negatively affects yields. The method of combing plants at the root is one of the new technologies of combine harvesting of grain crops. However, the main deterrent to the widespread introduction of new grain harvesting equipment remains the problem of harvesting stems combed at the root. Types of devices such as segment-type cutting device with conveyor mechanism, screw cutting device and rotary cutting device are the most suitable for harvesting stem stalks. Methods and means of harvesting the non- grain part of the crop with a cleaning combine are considered. The problem of improving the cutting device is solved, in which by modernizing the structural- technological scheme based on the set of structural elements, their mutual location and the presence of connections between them, increases the productivity of the cutting device, increases the reliability of the cutting process and rolls cut stems. The general method of choosing a cutting device depending on the crop being harvested and the technology of collecting cut stems is given.
Collection of non-grain part of harvest by computer type
Збирання незернової частини врожаю комбайном обчісувального типу / К. О. Шегеда, О. М. Шокарев, Б. В. Болтянський, О. О. Шокарев // Науковий вісник Таврійського державного агротехнологічного університету : електронне наукове фахове видання. Мелітополь : ТДАТУ, 2022. Вип. 12. том 2. C. 75-84.
Keywords: збирання зернових культур; обчісування рослин; різальний пристрій; harvesting cereals; combing plants; cutting unit